The Phenomenon of “The Perm disaster” of 1918 in the Assessment of Modern Researchers of the Civil War in Russia - I. V. Skipina; V. V. Moskovkin (Научный диалог, 2020)
The article is devoted to the peculiarities of presentation of the phenomenon of “Perm disaster” by modern researchers of the Civil War in Russia. The purpose of the article is to analyze publications published in the last decade on the history of the military operation near Perm in December 1918, to summarize and determine the prospects for studying this issue. It is noted that historians have established the causes, course and results of the operation. It is reported that today it is seen as a prologue to a cardinal change in the situation on the Eastern Front. The authors claim that as a result of the Perm operation, contemporaries witnessed not only the defeat of the Red Army, but also the manifestation of the power of the Bolshevik dictatorship. The conclusions made by researchers are summarized: Permian events led to an aggravation of the military, socio-economic, and political situation on the Eastern Front and had a negative impact on everyday life. It is shown how modern historians have determined the significance of these events for their participants: the Bolsheviks came to the decision to intensify terror, the white - to the conclusion that a general offensive was necessary, the population - to the understanding of the world as the most important life value. It is emphasized that the most promising in the study of the topic has become an integrated approach based on the rejection of politicization and myth-making of the revolutionary past.